Eksplorasi dan Revisi Tujuan Karier: Respon Individu ketika Pencapaian Karier Melampaui Target - Sari Zakiah Akmal (Jurnal Ilmiah Psikologi MIND SET, 2023)
There has been limited research on investigating young adults’ regulatory responses to the positive career goal discrepancies (current career progress ahead of career goal). In fact, it is important to further explore this topic to optimize young adults’ career potential. This study hypothesized that young adults who experienced positive career goal discrepancies would more likely engage in career exploration activities that would trigger upward career goal revisions. We tested that hypothesis by using a quantitative approach and a cross-sectional study. About 314 first-year undergraduate students (Mage = 18.63, SD = 0.81) was hired using the accidental sampling technique were participated in this study. The Positive Career Goal Discrepancy, The Career Exploration, and The Upward Career Goal Revision Scales were used to collect the data. The mediation analysis shows that positive career goal discrepancy trigger young adult’s to revise their career goal upward, both directly and indirectly via career explorations(range of 95% CI indirect effect [.007 - .019]). Young adults who experienced positive career goal discrepancies would engage in career exploration activities, which would trigger them to set a more challenging career goal. This result inform the career counsellor and practitioners on how to optimize young adults career potentials.